International Comparisons of Earnings Inequality for Men in the 1980 s - John Coder; Gordon Green; Paul Ryscavage; Brian Gran (Luxembourg Income Study (LIS), 1990)
LIS database is used to compare various nations' earnings distributions with respect of earnings inequality during the mid 1980's. The paper also addresses whether or not earnings inequality changed in some of these countries between the beginning of the decade and the mid-1980's.
Keywords: 330